Jews, Museums, and National Identities - Greenberg, Reesa (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2002)
Museums, particularly ethnographic museums, are paradigmatic sites for testing the limits of tolerance of, for, and within, minority cultures. In a discussion of European Jewish museums in Europe, I examine four inter-related variables as indices of tolerance: 1) a museum’s integration into the culture at large; 2) the inclusion of various Jewish ethnic and racial types; 3) the representation of women; and 4) the response to genocide.